Hyperglycosylated hCG and Its Free ß-Subunit Drives Malignancy (Journal of Analytical Oncology, 2018)
Tumor marker studies were conducted measuring 2,277 malignancies using a cut-off of 3 fmol/ml. As found 110 of 110 trophoblastic malignancies or 100% were positive for ß-core fragment an hCG serum degradation product. Just 949 of 2167 (44%) of non-trophoblastic or other cancers were positive using this 3 fmol/ml cut-off. When the cut-off of the assay was lowered to 0.1 fmol/ml, or lowered by 30-fold 100% of non-trophoblastic or other cancers were detected, or all cancers were detected.What do cancers secrete. Cancer were tested with three immunoassays, Immulite total hCG, B152 hyperglycosylated hCG and FBT11 free ß-subunit, serum of 34 trophoblastic cancers and 32 non-trophoblastic cancers were tested. A total of 34 of 34 trophoblastic cancer produced primarily hyperglycosylated hCG (B152 hyperglycosylated assay 96%±12% of Immulite), and 32 of 32 non-trophoblastic cancers produced primarily hyperglycosylated hCG free ß-subunit (B152 hyperglycosylated assay 102%±6.2% of Immulite, FBT11 free ß-subunit assay 128%±10% of Immulite).Seven independent laboratories each showed with a wide mixture of cancers (patient tissue and cancer cell lines) that ß-subunit promoted malignancy (cell growth, cell invasion and blockage of apoptosis) in cancer cells. I then showed that hyperglycosylated hCG and its ß-subunit promoted malignancy in 10 different cancer cell lines.I then tied my data and the seven independent laboratory data together and concluded that hyperglycosylated hCG and its ß-subunit drove malignancy in all or most cancers.